The influence of education level, halal awareness, and halal certification costs on halal certification decisions with religiosity as a moderating variable: A case study of MSMEs in Kudus Regency - Amalia, Widya Faidatul; Andni , Riyan (Universitas Islam Indonesia, 2023)
IntroductionCurrently, halal certification is crucial for Micro, Small, and Medium Enterprises (MSMEs). Halal certification, issued by BPJPH based on a fatwa from the Indonesian Ulema Council, acknowledges a product's halal status. Despite high education levels, strong halal awareness, and affordable certification costs, only a few MSMEs in the Kudus Regency have obtained halal certification. This study aims to analyze the influence of education level, halal awareness, and halal certification costs on the halal certification decisions of MSMEs in the Kudus Regency, with religiosity as a moderating variable.ObjectivesThe objective of this research is to analyze the effects of education level, halal awareness, and halal certification costs on halal certification decisions and to examine the role of religiosity as a moderating variable in these relationships. MethodThis quantitative study utilized data from 144 MSMEs in the Kudus Regency, which have not yet obtained halal certification. The data were analyzed using multiple linear regression with moderating effects using EViews. This study tested hypotheses regarding the direct and moderating effects of education level, halal awareness, and certification costs on halal certification decisions.ResultsThe findings indicate that educational level, halal awareness, and halal certification costs significantly influence halal certification decisions. However, religiosity did not moderate the relationship between these variables and halal certification decisions. Higher education levels bring greater awareness of the importance of halal certification, while increased halal awareness positively affects certification decisions. Certification costs are also a significant factor, with lower costs encouraging MSMEs to seek certification. ImplicationsThese results suggest the need for broader educational campaigns focused on the importance of halal certification in increasing MSME awareness. Governments and related institutions should consider providing subsidies or financial assistance to reduce certification costs. Enhancing educational and training programs on halal certification can also drive market demand for halal products.Originality/NoveltyThis research contributes to the understanding of the factors influencing halal certification decisions among MSMEs, highlighting the roles of education, awareness, and cost, while questioning the moderating effect of religiosity. It provides practical recommendations for policymakers to support MSMEs in achieving halal certifications.